2007
DOI: 10.1073/pnas.0606144104
|View full text |Cite
|
Sign up to set email alerts
|

Substrate interactions with human ferrochelatase

Abstract: Ferrochelatase, the terminal enzyme in heme biosynthesis, catalyzes the insertion of ferrous iron into protoporphyrin IX to form protoheme IX. Human ferrochelatase is a homodimeric, inner mitochondrial membrane-associated enzyme that possesses an essential [2Fe-2S] cluster. In this work, we report the crystal structure of human ferrochelatase with the substrate protoporphyrin IX bound as well as a higher resolution structure of the R115L variant without bound substrate. The data presented reveal that the porph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
106
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 37 publications
11
106
0
Order By: Relevance
“…Based on these results, it has been suggested that the mode of binding of N-MeMP to B. subtilis ferrochelatase may not reflect the proper substrate-binding mode. 22 However, our observation that N-MeMP bound to wild-type B. subtilis ferrochelatase could be metallated while in the complex with the His183Ala variant it could not, suggests strongly that the porphyrin is bound to the protein in a "productive" state.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Based on these results, it has been suggested that the mode of binding of N-MeMP to B. subtilis ferrochelatase may not reflect the proper substrate-binding mode. 22 However, our observation that N-MeMP bound to wild-type B. subtilis ferrochelatase could be metallated while in the complex with the His183Ala variant it could not, suggests strongly that the porphyrin is bound to the protein in a "productive" state.…”
Section: Discussionmentioning
confidence: 84%
“…In human ferrochelatase, the porphyrin is rotated by about 100° and buried by an additional 4.5 Å deeper into the active site cleft, relative to the position of N-MeMP bound to the B. subtilis enzyme. 22,23 The structures of the human enzyme also show that the porphyrin binding cleft is in a closed conformation as compared to the porphyrin-free protein, whereas in B. subtilis ferrochelatase the entrance to the cleft is more open after porphyrin binding. Based on these results, it has been suggested that the mode of binding of N-MeMP to B. subtilis ferrochelatase may not reflect the proper substrate-binding mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall these results demonstrate that this residue plays a role in multiple steps in the ferrochelatase mechanism. The dual role of this residue is also apparent from the E343K variant which binds and co-crystallizes with porphyrin (15), but is inactive (1).…”
Section: Eqnmentioning
confidence: 99%
“…However, the mode of binding of the true substrate, protoporphyrin, to human ferrochelatase is different as the substrate is rotated around by 100°and is accommodated approximately 5 Å deeper within the active site. Moreover, only a slight warp is observed in the plane of the macrocycle indicating that just minor ruffling of the tetrapyrrole is required to enhance metal insertion (19,20). The latter, therefore, represents a more accurate substrate/product binding site than that identified by the former inhibitor complex.…”
mentioning
confidence: 99%